Effect of Humidity and Impurities on the Electrochemical Window of Ionic Liquids and Its Implications for Electroanalysis - Doblinger, Simon; Donati, Taylor; Silvester-Dean, Debbie (AMER CHEMICAL SOC, 2020)
Replacing conventional aqueous-based electrolytes with room-temperature ionic liquids (RTILs) for electrochemical applications is a major research focus. However, in applications where RTILs are exposed to real-world environments, their hygroscopic nature affects their promising physicochemical properties, such as broad electrochemical windows (EWs) and high chemical stability. In this study, the electrochemical windows of nine commercially available RTILs have been determined on platinum thin-film electrodes in "dry"conditions (4.3-6.5 V) via cyclic voltammetry, and a systematic study over a wide humidity range (relative humidity (RH) between <1 and >95%) has been carried out. A significant reduction in the EW occurs even at low moisture contents (<10 RH%), which is especially evident for the most electrochemically stable ions in the study (i.e., [C4mpyrr]+, [FAP]-, and [NTf2]-). At saturated water levels, the electrochemical windows come close to that of water (approximately 2 V) regardless of the cation or anion structure, where the electrolyte behavior changes from "water-in-RTIL"to "RTIL-in-water."Additionally, the appearance of redox peaks from dissolved impurities inherent to the RTIL becomes more obvious with increasing water content. The effect of moisture on the electrochemical response of two model species where the presence of water does not alter the electrochemical mechanism, i.e., decamethylferrocene and ammonia, was also studied. For ammonia, the increase in current is not only caused by a change in the transport properties of the electrolyte (lower viscosity) but also by a shift in the anodic limit of the electrochemical window. This is believed to be the most detailed study of the effect of water on RTILs over a wide humidity range and emphasizes the importance of understanding the effect of water on voltammetric responses of dissolved species in RTILs under different environmental conditions.